Pragmatics Perspective: The Analysis of Illocutionary Act Found In Movie “Toy Story 1” - Kadek Devi Arshanti; Ni Wayan Swarniti (CV. Tirta Pustaka Press, 2023)
Pragmatics deals with the study of meaning based on several factors, such as speaker relevance, context relevance, listener inference, and even expression. It is hoped that this research can reveal speech acts commonly used in children's films, which children usually imitate and repeat in everyday life. This research is descriptive and qualitative. The source of the data in this study was movie scripts from an animated children's film entitled Toy Story 1. The data collection technique used in this study is observation. Data is collected through utterances uttered in the dialogue of the characters in the film. The most frequently obtained data are expressions. The data percentage of the expression was 27,7% or 10 data. The percentage of data obtained from representatives was 25% or 9 data. The percentage of data found from the directive was 25% or 9 data the same as the data found in the representative. The percentage of data from declarative was 13,8% or 5 data. The percentage of data found from commissive is 8,33% or 3 data. From some of the data found, commissive data has a small percentage, namely only 3 data.